Diagnostic and treatment methods of skeletal symptoms of haemophilia and education of patients regarding the disease – review study - Gorecka, Adrianna; Osial, Natalia (Journal of Education, Health and Sport, 2023)
Introduction. Haemophilia is a genetic haemorrhagic disorder that characterises with extensive and prolonged bleeding. In severe stages of the disease, joint haemorrhages may occur and eventually result in joint degeneration and haemophilic arthropathy. Aim of the study. Summary and evaluation of diagnostic and treatment methods of skeletal problems in patients with haemophilia. Review of patients’ knowledge about the disease. Material and methods. Review of the newest medical journal literature published on PubMed database. Results. Ultrasonography is a non-invasive imaging method used to diagnose acute hemarthrosis and early stages of joint damage. Magnetic resonance is a standard tool in evaluation and scoring of haemophilic arthropathy. X-rays and computed tomography can also be additionally used, but are ineffective in imaging soft tissue and cartilage. Substitution of clotting factors is a standard treatment in haemophilia which reduces the frequency of bleeding. Arthrocentesis, synovectomy for example radiosynovectomy are effective in case of joint disorders. Intra-joint injections of hyaluronic acid are also effective. In advanced stages of haemophilic arthropathy joint replacement is recommended. Majority of patients with haemophilia claim that they are sufficiently educated about their disease. Conclusion. Haemophilic arthropathy is a severe joint destructing condition that causes limited mobility, chronic pain and a reduced quality of life. Its early diagnosis and proper treatment is necessary to avoid total destruction of the affected joint. Multidisciplinary care of the patient is an approach of great importance. Education of patients about their disease and up-to-date treatment methods is necessary.